A Self‐Healing Dielectric Supramolecular Elastomer Functionalized with Aniline Tetramer. Issue 20 (24th September 2018) - Liu, Ling; Yan, Shu; Zhang, Liqun
Abstract: A new design strategy to produce a supramolecular elastomer with self‐healing and dielectric properties by synthesizing an aniline tetramer (AT)‐functionalized supramolecular elastomer (SE‐AT) is demonstrated. The termination of AT in the supramolecular system not only shortens linear amide molecular chain to decrease glass transition temperature but also destroys the crystallization to achieve amorphous structure. The SE‐AT provides two kinds of noncovalent bonding including π–π stacking and the hydrogen bond, which makes the material more easily healed. The SE‐AT20% can heal mechanical properties within 24 h at room temperature without any external stimulus. The dielectric constant shows a continuous increase overall with increasing AT content. The material exhibits good electro‐mechanical properties, which is attributed to a simultaneous increase in dielectric constant and decrease in modulus. The maximum actuated strain significantly increases with the increasing AT content and the SE‐AT20% reaches 10% at 1 V µm −1 . Moreover, SE‐AT exhibits the ability to regain actuated strain on the location of the mechanical damage after self‐healing. Abstract : A new design strategy to produce a self‐healing dielectric elastomer by synthesizing an aniline tetramer(AT)‐functionalized supramolecular elastomer (SE‐AT) is demonstrated. The SE‐AT exhibits an excellent self‐healing capability at room temperature and outstanding electro‐mechanical property at low electric field. Moreover, SE‐AT exhibits the ability to regain actuated strain at electric fields after self‐healing.